(3GdJMdjd GdeGdj (B:s (3eONd UfGYI GdbQGQGJ (B/s - (3TGcQ eMeO, efjQs ((3YeGf(B: s (3OGQ hGFd(B, s, 2005)
(3WHjYI GdJMdjd GdeGdj(B-(3COhGJ GdJMdjd GdeGdj(B-(3GdfSH GdYGdjI(B-(3JMdjd GdeQcR GdeGdj bUjQ GdCLd(B-(3JMdjd bGFeI GdJOabGJ GdfbOjI(B-(3GSJNOGe GdJMdjd GdeGdj aj GdJfHD HGdaTd GdeGdj(B-(3JMdjd JMdjd YdGbGJ GdJcdaI(B-(3GdMLe(B-(3GdQHM(B-(3JMdjd caGAI GdYed hOQLI GdQGaYI(B-(3JMdjd GdeQcR GdeGdj Whjd GdCLd hJcdaI GdJehjd(B.s
Keywords: (3GdJMdjd GdeGdjs